2019
DOI: 10.1111/jog.14129
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of post‐partum hemorrhage in women with a history of uterine artery embolization

Abstract: Aim: To evaluate pregnancy outcome and complications in subsequent pregnancies after severe post-partum hemorrhage (PPH) between women with and without a history of uterine artery embolization (UAE). Methods: Women who had a history of severe PPH, and delivered newborns at ≥22 gestational weeks in subsequent pregnancies were enrolled. Severe PPH was defined as blood loss volume of more than 2000 mL. Results: The blood loss volume (median 1581 mL) in women with UAE (n = 14) was significantly more than that in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Prior UAE is associated with an increased rate of placenta accreta spectrum and PPH during subsequent pregnancies (1416). In our study, one patient presented with placenta accreta that led to PPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior UAE is associated with an increased rate of placenta accreta spectrum and PPH during subsequent pregnancies (1416). In our study, one patient presented with placenta accreta that led to PPH.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated the effect of UAE on future fertility and demonstrated sufficient pregnancy outcomes (9)(10)(11)(12)(13). However, a few studies focused on an enhanced risk for placental disorders and PPH recurrence in subsequent pregnancies (14)(15)(16). As the rate of UAE has increased for PPH (17), detailed information on pregnancy outcomes, including complications, should be revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Оценке течения и исходов последующих после ЭМА беременностей и родов у пациенток с гипотоническим ПРК посвящены исследования ряда зарубежных авторов и описаны следующие осложнения: рецидив гипотонического ПРК -у 31,6%, врастание плацентыу 17,7-50% [25,[28][29][30]…”
Section: Discussionunclassified
“…UAE provides as a minimally invasive option for controlling postpartum hemorrhage (PPH) that is resistant to medical intervention [ 3 ]. Numerous studies have shown the reliability and effectiveness of UAE as a fertility-saving intervention for PPH [ 4 ]. However, problems following UAE, like uterine infection and ovarian malfunction, are thought to impact a woman's ability to conceive in the future and her ability to bear a child [ 5 ].…”
Section: Introductionmentioning
confidence: 99%